Negotiating with Iran - Amr G. E. Sabet (American Journal of Islam and Society, 2010)
In his preface to this book, Mark Bowden states that John Limbert is “the best American friend Iran had” (p. ix) and that the United States is “not a nineteenth-century-style imperial power bent on colonizing smaller nations.” Thus, Iranian suspicions of it as well as their suspecting (re)actions were “inexplicable.” This was particularly so as in the case when the United States became one of the “primary victims of Iran’s assault on international civility” (pp. x-xi). With this auspicious introduction, Bowden inaugurates Limbert’s study on how to negotiate with Iran ...